THE EFFECT OF WORKING CAPITAL TURNOVER AND RECEIVABLES TURNOVER ON PROFITABILITY IN TRANSPORTATION COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE PERIOD 2021-2024 - Muhammad Arul Andreandra; Kasmanto Miharja (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
The transportation sector in Indonesia is a crucial contributor to the national economy by facilitating the distribution of goods and public mobility. Although its contribution to Gross Domestic Product continues to increase, particularly post-pandemic, profitability in transportation companies has fluctuated and tended to be low. This indicates challenges in corporate financial management. Therefore, this study was conducted to analyze whether working capital turnover and accounts receivable turnover affect profitability in transportation companies listed on the Indonesia Stock Exchange for the 2021-2024 period. This study employed quantitative methods with purposive sampling, resulting in a sample of nine companies. The analytical methods employed included descriptive statistics, classical assumption tests, multiple linear regression, and hypothesis testing. The data used were secondary data in the form of financial reports. The results showed that working capital turnover had no significant effect on profitability, while accounts receivable turnover had a significant positive effect. Simultaneously, both variables significantly influenced profitability.